Tinjauan Penerapan Code of Conduct for Responsible Fisheries (CCRF) pada Alat Tangkap Sero dan Bagan Perahu di Perairan Tondonggeu, Kendari - Marni, Marni; Sara, La; Tadjuddah, Muslim (Jurnal Manajemen Sumber Daya Perairan, 2020)
Sustainability fisheries resources management is one of alternatives overcoming national economic crisis impact of Indonesia. The use of world wide fish capture according to the Code of Conduct for Responsible Fisheries (CCRF) principles is a way to maintain sustainability fisheries resources population. The aim of this study was to analyze stake trap and boat lift net fishing gears in Tondonggeu waters which had been used by fishermen according to CCRF criteria. The data collected was through interview and direct observation conducted from April to June 2018. The data collected consisted of species of fish, length of fish, fishing ground, fishing gears operation method, injury story of fishermen during the use of fishing gears, fish capture quality, main target of fish physical condition, by-catch fish quality, fish resources sustainability concerns, fish species ptotected, and response of local community on those fishing gears. The data obtained was analyzed according to the level of environmental friendly of fishing gears used i.e.> 80% (very much environmental friendly), 50 – 80% (environmental friendly), 25 – 50% (less environmental friendly), and < 25% (no environmental friendly). The result of study showed that those both fishing gears include fishing gears environmental friendly. However, boat lift net is very much environmental friendly with the score is 73,33% and 88.33%, respectively.Key words: Boat lift net, Code of Conduct for Responsible Fisheries, Stake trap